Rapid Eye Movements in Sleep Furnish a Unique Probe Into Consciousness - Hong, Charles C.-H.; Fallon, James H.; Friston, Karl J.; Harris, James C. (Frontiers in Psychology, 2018)
The neural correlates of rapid eye movements (REMs) in sleep are extraordinarily robust; including REM-locked activation in the retrosplenial cortex, the supplementary eye field and areas overlapping cholinergic basal nucleus. The phenomenology of REMs speaks to the notion that perceptual experience in both sleep and wakefulness is a constructive process – in which we generate predictions of sensory inputs and then test those predictions through actively sampling the sensorium with eye movements. On this view, REMs during sleep may index an internalized active sampling or ‘scanning’ of self-generated visual constructs that are not constrained by visual input. If this view is correct, it renders REMs an ideal probe to study consciousness as “an exclusively internal affair” (Metzinger 2009). In other words, REMs offer a probe of active inference – in the sense of predictive coding – when the brain is isolated from the sensorium in virtue of the natural blockade of sensory input during REM sleep. REMs are temporally precise events that enable powerful inferences based on timeseries analyses. As a natural, task-free probe, [REMs] could be used in non-compliant subjects, including infants and animals. In short, REM constitutes a promising probe to study the ontogenetic and phylogenetic development of consciousness and perhaps its abnormal development in schizophrenia and autism, which have been considered in terms of aberrant predictive coding.